2016
DOI: 10.1177/0266242615615185
|View full text |Cite
|
Sign up to set email alerts
|

Tax compliance over the firm life course

Abstract: This article provides a new model of tax compliance over the firm life course, focusing on the dynamics in the underlying motivations and capacities for tax compliance. We review and structure the relevant literature on the early life course of firms: the traditional stages of growth models and a less deterministic dynamic state model of developmental phases. Building on these insights on the changing nature of the firm and the role of the founder-entrepreneur, we construct a new model of tax compliance over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 54 publications
1
9
0
1
Order By: Relevance
“…This is in line with certain findings in the literature that emphasize that the acceptance of underground economic activities is often correlated with the acceptance of one's own tax evasion (Molero & Pujol, 2012). It also supports the literature that points to tax compliance as an instrumental motivation for more mature small firms, but not necessarily larger ones (Stam & Verbeeten, 2017). In a Nigerian context, it loops in with research that found that micro-enterprises that registered generally perform better (Adekunle, 2011).…”
Section: Estimation Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This is in line with certain findings in the literature that emphasize that the acceptance of underground economic activities is often correlated with the acceptance of one's own tax evasion (Molero & Pujol, 2012). It also supports the literature that points to tax compliance as an instrumental motivation for more mature small firms, but not necessarily larger ones (Stam & Verbeeten, 2017). In a Nigerian context, it loops in with research that found that micro-enterprises that registered generally perform better (Adekunle, 2011).…”
Section: Estimation Resultssupporting
confidence: 89%
“…We believe this misses the centrality of businesses development to a small firm's tax decisions and perceptions. Taking firm heterogeneity as a starting point rather than a control variable brings in a better focus on the firm's life cycle, from inception over survival to growth and expansion (Stam & Verbeeten, 2017). Business development is at the centre of a firm's assessment of its trade-offs and its position towards the community, government, and country.…”
Section: Small Firms Tax Morale and Its Explanatory Dimensionsmentioning
confidence: 99%
“…Developing this logic, a number of scientists allocated such a characteristic as the tax potential (Stam & Verbeeten, 2017), which even at the micro level is interpreted broadly, ranging from hidden, implicit overpayments of taxes to the budget, which is a reserve of the organization to improve its financial results and ending with the optimal amount of taxes and fees in an ideal for a particular organization of the tax system. According to the approaches of some economists, tax potential is the ratio of the amounts paid to the https://doi.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, there has been an increasing trend to examine the relationship between a firm's life cycle and different aspects (Habib and Hasan, 2019), These are: the key determinants of firm life cycle (Agarwal and Audretsch, 2001;Jenkins et al, 2004;Mata and Freitas, 2012;Warusawitharana, 2018); the value relevance of the firm's financial information (Black, 2003;Habib, 2010;Hribar and Yehuda, 2015;Vorst and Yohn, 2018;Dickinson et al, 2018); the firm's tax posittion (Anandarajan et al, 2010;Stam and Verbeeten, 2017;Hasan et al, 2017); corporate governance (Chiang et al, 2013;Li and Zang, 2018) ; cash holding (Drobetz et al, 2015, Alzoubi, 2019; auditing (Hossain et al, 2019) ; corporate social responsibility (Hasan and Habib, 2017;Lee and Choi, 2018;Hsu and Chen, 2018); and the quality of the firm's financial reporting as measured by different proxies such as sustained earnings (Suberi et al, 2012;Drake, 2012), conservatism (Abdullah and Mohd-Saleh, 2014;Hansen et al, 2018) and readability and tone (Bakarich et al, 2019)).…”
Section: Firm's Life Cycle Stagesmentioning
confidence: 99%